Effect of Task Through Test Rankings Based Learning Model REACT to the Achievement of Physics - Amirudin, Dessy; Kusdiwelirawan, A.; Soenarto, Y. (Program Studi Pendidikan Fisika UHAMKA, 2017)
The aim of this study is to find out the effect of test-based on the ranking task through the learning model of REACT (relating, experiencing, applying, cooperating, and transferring) toward physics learning achievement. The research is held in 105 Senior High School in Jakarta on the even semester of 2015-2016. The population in this research is around 32 students roommates are all investigated. The sampling technique that use is purposing sampling technique. This research use quantitative research. After the data is distributed normally and the homogeneity based on the normality test and homogeneity, the data that is gained the lcount < ltable (0.11 < 0.156). The hypothesis test is done by using the t-test and the result tcount > ttable (8.575 > 1.689) (on the 0.05 significant extent) or 8.575 > 2.456 (on the 0.01 significant extent) which means H0 is rejected, H1 is therefore accepted. All in all this research could bring the effect of test-based on the ranking task learning model through the REACT toward physics learning achievement.